The consequences of the COVID-19 pandemic on perceived stress in clinical practice: experience of doctors in Iraqi Kurdistan - Abdulah Deldar Morad; Mohammed Ayad Ahmad (Romanian Journal of Internal Medicine, 2020)
Introduction. The healthcare workers are at high risk of developing stress-related problems during outbreaks. This study aimed to explore the perceived stress and its relation to the duration of dealing with COVID-19 patients in medical doctors.